The Polarization and Depolarization Current Characteristics of Natural Ester Stressed by Partial Discharge - Maneerat, Noppadol; Makmork, Kawee; Kittikhuntharadol, Yannaphol; Suksai, Nattapat; Chusang, Thanapat; Pattanadech, Norasage (My University, 2020)
This paper represents the polarization and depolarization current (PDC) of the natural ester stressed by partial discharge (PD). The needle-plane electrode was used to simulate corona discharge in natural ester. Besides, the needle electrode as a high voltage electrode placed on the 8 hours natural ester impregnated pressboards and the plane electrode as a grounded electrode were used to simulate the surface discharge. To simulate the internal discharge, the plane-plane electrode inserted with various condition impregnated pressboards were experimented. PD phenomena were simulated in the natural ester container for 1, 3, and 6 months. Then the PD-stressed natural ester was used as the liquid specimen for polarization and depolarization current measurement. It was found that the PDC characteristics of natural ester undergone with various PD types were obviously different.
Keywords: depolarization current; natural ester; partial discharge; polarization current